Impacto del COVID-19 en el crecimiento económico de la región Loreto, período 2019 - 2020 - Angulo Vela, Andrea (2022)
The COVID-19 pandemic has seriously affected the whole world, showing a great impact on different aspects of society, especially the economy and health, our country, Peru, was one of those that had the most impact since the pandemic exponentially exceeded the capacity of the health system and the actions of the state. Given this situation, this research work was developed to respond to the problem: What is the impact of COVID-19 on the economic growth of the Loreto region, period 2019-2020? which allowed to develop the following specific problems; How has the behavior of COVID -19 been in the Loreto region, period 2019 - 2020? What is the possible impact that COVID -19 may have on the economic growth of the Loreto region, period 2019 - 2020? What results does economic growth present in the Loreto region, period 2019 - 2020? Likewise, this study seeks to meet the general objective of studying the impact of COVID-19 on the sustainable economic growth of the Loreto region, period 2019 - 2020, and with the specific objectives; describe the behavior of COVID -19 in the Loreto region, period 2019 - 2020, describe the possible impact that COVID -19 could have on the economy of the Loreto region, period 2001 - 2009, and determine the results presented by economic growth in the Loreto region, period 2019 - 2020. The present study is non-experimental, longitudinal and comparative in nature. The issue of why COVID-19 has had a high impact on the economic and labor field of study, and particularly in the Loreto region, is important. The accumulated amount of damage in the companies that has been registered since its validity, 2019, until 2020, is significantly large. To this is added, that it is a pandemic that still has no end.